2017
DOI: 10.1080/14786419.2017.1295239
|View full text |Cite
|
Sign up to set email alerts
|

Two new sesquiterpene lactone glycosides from Cnicus benedictus

Abstract: Two new sesquiterpene lactone glycosides, namely melitensin 15-O-β-D-glucoside (1) and 11β,13-dihydrosalonitenolide 15-O-β-D-glucoside (2), along with eight known compounds (3-10) were isolated from the aerial part of Cnicus benedictus L. Their structures were elucidated from analyses of extensive spectroscopic data. Compounds 1-6 all possessed an α-methyl-γ-lactone moiety. Moreover, compound 5 exhibited moderate activity against the growth of Aspergillus fumigatus, with IC values of 17.67 μg mL.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…Apigenin 7- O -glucoside, astragalin, arctiin, nortracheloside, luteolin, sitogluside, and cnicin were isolated from the CBE according to the previous protocols [ 14 , 15 , 16 , 17 , 18 ]. All of the aforementioned compounds were purchased (Sigma Aldrich, Santacruz Biotech, USA and BioCrick, Sichuan Province, P. R. China) to ensure the antiviral’s maximum possible purity for the in vitro testing.…”
Section: Methodsmentioning
confidence: 99%
“…Apigenin 7- O -glucoside, astragalin, arctiin, nortracheloside, luteolin, sitogluside, and cnicin were isolated from the CBE according to the previous protocols [ 14 , 15 , 16 , 17 , 18 ]. All of the aforementioned compounds were purchased (Sigma Aldrich, Santacruz Biotech, USA and BioCrick, Sichuan Province, P. R. China) to ensure the antiviral’s maximum possible purity for the in vitro testing.…”
Section: Methodsmentioning
confidence: 99%
“…The phytochemistry of C. benedicta preparations has been relatively well reported. The plant is relatively rich in sesquiterpenoid glycosides, particularly cnicin (0.2-0.7%), polyacetylen and absinthin, 52 as well as lower relative amounts of salonitenolide and artemisiifolin. These compounds are believed to be largely responsible for the bitter flavour of C. benedicta extracts.…”
Section: Phytochemistrymentioning
confidence: 99%
“…59 A recent study has also identified two new sesquiterpene lactone glycosides, melitensin 15-O-β-D-glucoside (Figure 2d) and 11β,13dihydrosalonitenolide 15-O-β-D-glucoside (Figure 2e). 52 Interestingly, dried C. benedicta plant material, volatile oil produced from the leaves, and isolated cnicin all have potent antibacterial activity against multiple pathogenic species (Newall et al, 1996). 54 The sesquiterpene lactone structure of cnicin allows it to form covalent bonds with bacterial proteins, thereby disrupting the bacterial membrane structure and function.…”
Section: Sesquiterpene Lactonesmentioning
confidence: 99%